The labor market in New Zealand, 2000-2017 - David C. Maré (IZA World of Labor, 2018)
New Zealand is a small open economy, with large international labor flows and skilled immigrants. Since 2000, employment growth has kept pace with strong migration-related population growth. While overall employment rates have remained relatively stable, they have increased substantially for older workers. In contrast, younger workers as well as the Maori and Pasifika ethnic groups experienced a sharp decline in employment rates and a rise in unemployment around the time of the global financial crisis. Wage gains have been modest and there has been a compression of earnings differentials by gender as well as by skill.
Keywords: J01; R00; 330; New Zealand; immigration; wages; unemployment; skill premium; gender gap